Investigação sobre a sobrevivência das empresas beneficiárias de incentivos fiscais no Ceará no período de 2005 A 2010 - Teixeira, Ricardo Santos (2012)
The purpose of this study is to analyze the survival of companies located in the State of Ceara and beneficiary of tax incentive within the Industrial Development Fund, specifically within the Industrial Development Incentive Program. Such benefit was created in 1979 and is currently the main fundraising tool of the new companies or the expansion tool of the existing companies in the State.The statistical technique of survival analysis of the nonlinear KAPLAN-MEIER nonparametric method was used, comparing the results of the beneficiary companies with the results of the non-beneficiary companies within the Industrial Development Fund/Industrial Development Incentive Program. The study took into consideration the location, the economic activity developed, the percentage of benefit and the turnover of the companies.The results demonstrate that the survival of the beneficiary companies is clearly superior to that of the non-beneficiary companies regardless their location, economic activity or size. The study also points out that segments of activity in which even the beneficiary companies present low survival indicators shall be subject to a scrutinized analysis by policy makers in the development of the State.